Development of E-Module for Plant Physiology Courses Based on Problem Based Learning to Increase Student's Critical Thinking Skills on Nutrition, Transportation and Photosynthesis - Inayah, Ilul; Gofur, Abdul; Balqis, Balqis (BIOEDUKASI, 2024)
This development research aims to develop, test the validation, practicality and effectiveness of e-modules in improving students' critical thinking skills for plant physiology courses. The material used in the implementation stage focuses on the material of Nutrition and Nutrient Transport in Plants. The method used Research and Development (R&D) development using the Lee & Owens model development design. The research was conducted at the State University of Malang on students majoring in biology education semester 3 totaling 33 experimental class students and 33 control class students. The results obtained from material validation are 100% with very valid criteria. Furthermore, media validation is 95.47% with very valid criteria, practitioner validation with a percentage value of 97.27% with very valid criteria. Practicality test averaged 96% including very practical criteria. The effectiveness test was obtained through the e-module implementation stage with the Nonrandomized Control-Group Pretest-Posttest Design research design using the N-gain score calculation which was 0.70 with high criteria on experimental class. 0.29 for control class which was on low criteria. Based on the test results that have been carried out, the development of e-modules based on Problem-based learning in critical thinking skills is said to be valid, practical, and effective in improving students' critical thinking skills.